FORMULATION AND IN VITRO IN VIVO EVALUATION OF BOSENTAN PELLETS FOR PROLONGED DRUG RELEASE - Karra, Narender; P, Narayana Raju; R, Sivakumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to develop extended release (ER) pellets of Bosentan, an endothelin receptor antagonist using fluid bed processor (coating). Method: The ER drug pellets of Bosentan were prepared using fluid bed coating. These drug-loaded pellets were further coated with ethyl cellulose of two viscosity grades and Eudragit as rate controlling polymers individual and in combination, hypromellose as pore former and binder, acetyl tributyl citrate as plasticizer, and magnesium stearate as anti-adhering agent. Results: The drug release was extended up to 24 h, and the drug release was mainly depends on the polymer type and polymer proportion. In vivo study of Bosentan, ER pellets were performed in healthy rabbits (New Zealand, White) of either sex weighing (3.0–3.3 kg) and were divided into two separate groups, each group consisting of 6 animals. Maximum plasma concentration (Cmax), maximum time (Tmax), area under the curve (AUC0-t), elimination rate constant (Kel), and half-life (T1/2) were studied for optimized formulation. Formulation was releasing the drug for a prolonged period of time. Conclusion: By the above results, it was observed that the prepared pellets could release the drug for an extended period when compared with the conventional dosage form of Bosentan, optimized formulation was shown longer half-life and Cmax indicates its acceptability. Finally, ER pellets of Bosentan were prepared for the treatment of pulmonary artery hypertension by fluid bed processor.